Measuring Soil Fertility under Hagenia abyssinica (Bruce) J. F. Gmel by the Biotest Method - Biruktayet Assefa; Gerhard Glatzel (International Journal of Agronomy)
The experiment was conducted at the Forestry Research Center, Ethiopia in 2008. Soil was sampled under the canopy of Hagenia abyssinica and from farmland area adjacent to the forest to measure fertility of soils by using the biotest with linseed (Linum usitatissimum L.), barley (Hordeum vulgare L.), and wheat (Triticum aestivum L.) as indicators. The experimental design was a completely randomized design comprising of 20 seedlings per study site. Seeds were seeded into polythene plastic bags. Seedling emergence, germination, and survival rate were recorded. Plant height and root collar diameter were measured. Final weight of fresh biomass was measured, and each component was oven-dried at 70°C. Dry weight was recorded at constant weight. Significant differences (P<.05) were observed between soil treatments. Plants grown on Hagenia-influenced soils attained better performance, suggesting the beneficial role of Hagenia abyssinica in enhancing soil fertility status which in turn results in higher productivity.